The Maryland Colony - Fradin, Dennis B. (Chicago : Childrens Press, 1990)
Examines the history of Maryland, from its colonization by England to the early years of its statehood. Includes brief biographical sketches of key figures.
Includes index.
Keywords: Maryland -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; Maryland -- History -- Colonial period, ca. 1600-1775 -- Biography -- Juvenile literature; Maryland -- History -- Revolution, 1775-1783 -- Juvenile literature; Maryland -- History -- Revolution, 1775-1783 -- Biography -- Juvenile literature; Maryland -- History -- Colonial period, ca. 1600-1775.; Maryland -- History -- Revolution, 1775-1783.